2008
DOI: 10.1196/annals.1448.021
|View full text |Cite
|
Sign up to set email alerts
|

Methylation‐Based Analysis of Circulating DNA for Breast Tumor Screening

Abstract: The applicability of cyclin D2 and RARbeta2 methylated markers for the development of a breast tumor screening assay was evaluated. Overall, 76 volunteers (mean age, 50.4 years), including clinically healthy women and women with breast lesions, were enrolled in a blind study of methylation of the cyclin D2 and RARbeta2 genes. Methylation-specific PCR (MSP) was conducted using total circulating DNA (cirDNA) from the blood, including the cell-free and cell-surface-bound DNA fractions. Only 1 of the 25 women of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The promising way to increase the sensitivity of the cirDNA-based assay was recently developed by group of Laktionov, who performed MSP using cirDNA extracted from plasma and eluates from the surface of blood cells [48,147]. The authors reported the presence of tumor-associated methylated genes in the cell-surface-bound DNA (csbDNA).…”
Section: Cirdna Methylation-based Assay Developmentmentioning
confidence: 98%
See 1 more Smart Citation
“…The promising way to increase the sensitivity of the cirDNA-based assay was recently developed by group of Laktionov, who performed MSP using cirDNA extracted from plasma and eluates from the surface of blood cells [48,147]. The authors reported the presence of tumor-associated methylated genes in the cell-surface-bound DNA (csbDNA).…”
Section: Cirdna Methylation-based Assay Developmentmentioning
confidence: 98%
“…The authors reported the presence of tumor-associated methylated genes in the cell-surface-bound DNA (csbDNA). Moreover, tumorrelated methylated forms of three genes (RAR 2, RASSF1A and HIC-1) were much more frequently evaluated in the cell-surface-bound circulating DNA compared with cell-free plasma cirDNA in breast tumorbearing patients [147]. The sensitivity of gastric cancer detection by MSP assays was increased significantly when cirDNA, extracted from plasma, and csbDNA were used as the template for MSP [48].…”
Section: Cirdna Methylation-based Assay Developmentmentioning
confidence: 99%
“…Aberrant methylation of CpG islands within the promoters and 5’-end regulatory regions of genes is increasingly being recognized as a frequent epigenetic modification and has been associated with transcriptional silencing of gene expression in mammalian cells [ 5 ]. Recent studies have demonstrated that epigenetic changes of cancer-related genes due to the methylation of gene promoter regions are early events in human carcinogenesis [ 6 7 ]. The human retinoic acid receptor beta2 (RARβ2) is a member of the nuclear receptor super-family and plays a key role in modulating the effects of retinoic acid (RA) on cell growth and differentiation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of cyclin D2 and RAR 2 methylated markers for the development of a breast tumor-screening assay showed mixed results [200]. Forty two per cent of the patients with primary diagnosis of breast fibroadenoma showed an aberrant methylation of at least one of tested genes in the circulating DNA though 33 % of patients with breast lesions not diagnosed as fibroadenoma (mastopathy) also displayed methylation.…”
Section: Breast and Ovarian Cancersmentioning
confidence: 95%